MODEL PENYERAPAN OBAT UNTUK INTERVAL DAN DOSIS BERBEDA - WIDANA, I NYOMAN (Jurnal Matematika; Vol 1 No 1 (2010), 2012)
This article will discuss the accumulated quantity of the drug in the bloodstream of the two administered methods of the drug. The first method the drug is administered every 12 hours with a dose of 12.5 mg, whereas for the second method the drug is administered every 24 hours with a dose of 25 mg. The calculations show that the second method accumulates more drugs in the bloodstream than the first method.
Keywords: drug absorption, drug dose, drug accumulation.